How Do Obstetric and Neonatology Teams Communicate Prior to High-Risk Deliveries? - Sundgren, Nathan C.; Suresh, Gautham K. (American Journal of Perinatology, 2018)
Background Improving communication in healthcare improves the quality of care and patient outcomes, but communication between obstetric and neonatal teams before and during a high-risk delivery is poorly studied.Study Design We developed a survey to study communication between obstetric and neonatal teams around the time of a high-risk delivery. We surveyed neonatologists from North America and asked them to answer questions about their institutions' communication practices.Results The survey answers revealed variations in communication practices between responders. Most institutions relied on nursing to communicate obstetric information to the neonatal team. Although a minority of institutions used a standardized communication process to summon neonatology team or to communicate in the delivery room, these reported higher rates of information sharing and greater satisfaction with communication between services.Conclusion Standardized communication procedures are an underutilized method of communication and have the potential to improve communication around high-risk deliveries.
Keywords: communication; hand off; birth; obstetrics; neonatology